2006
DOI: 10.1128/cvi.00056-06
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus NS Vectors Expressing theMycobacterium tuberculosisESAT-6 Protein Induce CD4+Th1 Immune Response and Protect Animals against Tuberculosis Challenge

Abstract: Infection with Mycobacterium tuberculosis remains a major cause of morbidity and mortality all over the world. Since the effectiveness of the only available tuberculosis vaccine, Mycobacterium bovis bacillus CalmetteGuérin (BCG), is suboptimal, there is a strong demand to develop new tuberculosis vaccines. As tuberculosis is an airborne disease, the intranasal route of vaccination might be preferable. Live influenza virus vaccines might be considered as potential vectors for mucosal immunization against variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 43 publications
0
44
0
2
Order By: Relevance
“…Although we show proof of principle that at least three SIV-specific CD8 T-cell responses (one Gag response and two Tat responses, all presented by Mane-A*10) can be boosted simultaneously by this recombinant influenza virus strategy, it could be cumbersome to construct sufficient numbers of influenza virus vectors to broadly cover relevant HIV/SIV T-cell epitopes in outbred populations. Expression of whole heterologous proteins from influenza virus proteins is technically possible and has been achieved with expression of the enhanced green fluorescence protein, interleukin-2, and tuberculosis proteins (21,37,56); however, the stability of such vectors will require careful study. We are currently constructing influenza virus vectors expressing whole SIV proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although we show proof of principle that at least three SIV-specific CD8 T-cell responses (one Gag response and two Tat responses, all presented by Mane-A*10) can be boosted simultaneously by this recombinant influenza virus strategy, it could be cumbersome to construct sufficient numbers of influenza virus vectors to broadly cover relevant HIV/SIV T-cell epitopes in outbred populations. Expression of whole heterologous proteins from influenza virus proteins is technically possible and has been achieved with expression of the enhanced green fluorescence protein, interleukin-2, and tuberculosis proteins (21,37,56); however, the stability of such vectors will require careful study. We are currently constructing influenza virus vectors expressing whole SIV proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These vaccine candidates are capable of inducing the enhanced Th1 systemic and the local mucosal immune response at the infection entry. The current research data prove that the vector technology based on the modification of the NS segment of influenza virus enables the generation of highly immunogenic recombinant virus strains that express the foreign sequences from the NS1 reading frame [90][91][92][93][94][95][96]. Clinical trials showed that viruses with the modified NS gene are safe and highly immunogenic [97].…”
Section: Resultsmentioning
confidence: 99%
“…Такие вакцины способны вызывать усиленный Тh1 системный и локальный мукозальный иммунный ответ во входных воротах инфекции. Полученные к настоящему времени ре-зультаты свидетельствуют, что векторная технология на основе модификаций сегмента NS вируса гриппа позволяет получать высокоиммуногенные рекомби-нантные штаммы, экспрессирующие посторонние антигенные последовательности с рамки считывания белка NS1 [90][91][92][93][94][95][96]. Вирусы с модифицированным ге-ном NS прошли клинические испытания, в которых показана их безопасность и высокая иммуногенность [97].…”
Section: зак лючениеunclassified